The carbon footprint of young-beef cattle finishing systems in the Eastern Plains of the Orinoco River Basin of Colombia - Ramírez Restrepo, Carlos Alberto; Vera-Infanzón, Raul R.; Rao, Idupulapati M. (Frontiers Media, 2023)
Introduction: Previous research has shown increased productivity amongst sown grass pastures compared to native savanna pastures by year-round grazing for fattening of adult and young Brahman (Bos indicus)-bred cattle in the well-drained native savanna ecosystem of the Colombian Orinoquía. But there is limited information on the carbon footprint (CF) of commercial young-Brahman heifers and steers reared throughout life on well-managed Brachiaria decumbens Stapf pastures.